Особенности формирования иммуноморфологического комплекса желудка при антигенном раздражении - Евтушенко, В.М.; Ключко, С.С. (Таврический медико-биологический вестник, 2013)
В дослідженні встановлені зміни у формуванні клітинної популяції лімфоїдних скупчень шлунка щурів при антигенній стимуляції. В экспериментальній группі у всі періоди постнатального развитку склад лімфоцитів перевищує контрольні показники. The study has established changes of the cell population formation inthe stomach lymphoid clusters of rats with antigen stimulation. In the experimental group, at all the periods of the postnatal development the number of lymphocytes exceed the benchmarks.